Chemical Characterization and Biological Activity of Varronia curassavica Jacq. Essential Oil (Boraginaceae) and In Silico Testing of α-Pinene - José Thyálisson da Costa Silva; Viviane Bezerra da Silva; Sabrina Bezerra da Silva; Maria Ivaneide Rocha; Adrielle Rodrigues Costa; Jailson Renato de Lima Silva; Marcos Aurélio Figueirêdo dos Santos; Maria Elizete Machado Generino; Jeovane Henrique de Souza; Maraiza Gregorio de Oliveira; Clara Mariana Gonçalves Lima; Raimundo Luiz Silva Pereira; et al. (Analytica)
Multidrug-resistant bacteria have complicated the treatment of gastrointestinal diseases; their microbial resistance stems from the indiscriminate use of medications and the transfer of resistance genes. Varronia curassavica Jacq., a plant traditionally used to treat rheumatic and gastrointestinal diseases in underserved populations, has sparked interest as a potential source of antimicrobial compounds. This study aimed to investigate the chemical composition and antibacterial effects of V. curassavica essential oil and to evaluate its toxicity in Drosophila melanogaster. The essential oil was extracted through hydrodistillation and its chemical composition was determined using GC-MS. Antibacterial tests were performed with microdilution. The results showed the presence of major compounds including α-pinene and β-caryophyllene. The essential oil did not show relevant MIC, but it enhanced the effects of the antibiotics, gentamicin, norfloxacin, and oxacillin. It exhibited no toxicity and did not affect geotaxis, even at high concentrations. The in silico analysis of α-pinene revealed low toxicity; however, its permeability to the BBB shows that caution is needed in its application. These results indicate that the essential oil of V. curassavica shows promising potential in enhancing pharmaceuticals to prevent increased bacterial resistance. In addition, it demonstrated safe aspects when tested on D. melanogaster.